PyCharm productivity and debugging techniques. (Packt Publishing, 2022)
PyCharm is a dedicated Python Integrated Development Environment (IDE) providing a wide range of essential tools for Python developers, tightly integrated to create a convenient environment for productive web and data science development. The course covers the following sections: Section 1 is about the introduction and helpful notes for the course. Section 2 discusses the process of managing and customizing your PyCharm workspace. In section 3, you will look at editing and formatting with ease in PyCharm, which offers a detailed view of how PyCharm supports the process of developing Python applications. In Section 4, you will look at version control with Git in PyCharm, including a theoretical discussion about what version control is and why it is important. Section 5 focuses on the use of PyCharm to streamline processes in programming such as testing, debugging, and profiling. In the next section, you will look at web development with JavaScript, HTML, and CSS. In the final section of the course, you will understand Integrating Django in PyCharm, which introduces Django, the premier web development framework in Python. By the end of the course, you will have learned everything about PyCharm productivity and debugging techniques. What You Will Learn Customize PyCharm Theme and Editor Install and manage Python packages with PyCharm Code refactoring and renaming Build PyCharm documentation Learn the process of converting and exporting functions Explore Git version control built-in PyCharm Audience This course is for back-end software engineers and front-end developers. It can also be taken by computer science students and everyone who wants to learn to program. No prior knowledge of Python is required, only a desire to learn PyCharm IDE. About The Author Martin Yanev: Martin Yanev is an internationally acclaimed aerospace software engineer. He holds a bachelor's degree in aeronautical engineering and a master's degree in aerospace dynamics. He is an associate member of the Royal Aeronautical Society in the United Kingdom. He is ISTQB certified with solid experience in systems test and integration. He became adept at programming skills in the past seven years by developing and testing complex software algorithms for aerospace applications. He is currently involved in the Single European Sky Project, which aims to increase the European airspace capacity by applying cutting-edge air traffic management systems.